1978
DOI: 10.1172/jci109182
|View full text |Cite
|
Sign up to set email alerts
|

Renal Net Glucose Release In Vivo and Its Contribution to Blood Glucose in Rats

Abstract: A B S T RThe results indicate that the net glucose release by the kidney in vivo in normal fed rats was 0.75+0.13 mg/dl per min, and that its contribution to blood glucose was 25.9±5.0%. When unilateral nephrectomy was performed, under the same conditions, renal net glucose release was one-half of that in rats with two intact kidneys, which indicates the quantitative accuracy ofthe isotope-dilution method employed in this study.In rats starved for 24 h, the renal net glucose release increased to 0.99+0.08 mg/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
1
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(49 citation statements)
references
References 22 publications
(28 reference statements)
3
44
1
1
Order By: Relevance
“…In 1978, Kida et al [32] found a renal contribution of 25 % to systemic glucose production in rats by injecting a bolus of [ ]glucose concentration following hepatectomy. In intact animals the isotopic net balance approach was not employed until recently, when a significant renal uptake of glucose was shown in dogs accounting for as much as 30 % of glucose removal from the circulation under postabsorptive conditions [11,12].…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1978, Kida et al [32] found a renal contribution of 25 % to systemic glucose production in rats by injecting a bolus of [ ]glucose concentration following hepatectomy. In intact animals the isotopic net balance approach was not employed until recently, when a significant renal uptake of glucose was shown in dogs accounting for as much as 30 % of glucose removal from the circulation under postabsorptive conditions [11,12].…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…In alloxan-diabetic rats renal gluconeogenesis was increased twofold compared to normal rats [32]. Several issues regarding the underlying mechanism, however, have remained controversial.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation
“…The statistical difference between diabetic and lean rats was measured by the unpaired t test: *P Ͻ 0.05. which is responsible for the stimulation of gluconeogenesis in renal cortical slices prepared from rats that have type 1 diabetes (31-33), can be ruled out. Although insulin has been shown repeatedly to inhibit gluconeogenesis in the human kidney in vivo (7,9,13,14) and in one study in the rat kidney in vivo (34), it is unlikely that it did so by a direct mechanism that altered gene expression because experiments that have been performed in the rat kidney indicate that insulin has no direct effect on the activity or synthesis of phosphoenolpyruvate carboxykinase in the kidney of diabetic rats (32,35). Moreover, our study shows that insulin does not inhibit glucose synthesis from lactate in isolated kidney tubules (Table 3).…”
Section: Factors Responsible For Long-term Stimulation Of Renal Glucomentioning
confidence: 99%
“…This implies that tracer-determined GP cannot simply be taken to be liver derived, and data must be inter- (1) showed a more sensitive response of the kidney to insulin than earlier studies (3,5). In line with this, McGuinness et al (2) found that renal GP in the dog also responded to stress hormone infusion.…”
mentioning
confidence: 95%